Evaluation of the Implementation of Boarding School Program in an Effort to Enhance the Achievement of a Solution in Man 1 City Bandung - Basyari, Achmad Muharam (Edumaspul: Jurnal Pendidikan, 2024)
The background of this research is the presence of strategic issues related to the quality of dormitories that need to be taken into account for the effectiveness of maintenance of dormitory in the future. The evaluative research with this qualitative approach took a case study on a boarding school Al Murabby MAN 1 City Bandung. The data and information used in this study were obtained from the thoughts of the educators, nurses, managers, experts, and related officials, as well as through the analysis of the maintenance of dormitories in MAN 1 Kota Bandung. The results of the research showed that first, in the context assessment, the madrasah assessed needs, problems, opportunities, and assets as the basis for setting and evaluating goals and priorities. Second, in input assessments, the Madrasah identified and evaluated various approaches and alternative plans to meet the identified needs and the objectives set. Third, in process assessment the school monitored, documented, and provided feedback to strengthen the implementation of the program. Fourth, in product assessment of the product, it identifies and assessed the desired and unwanted results, both positive and negative. Keywords: Evaluation, Bed and Breakfast, Mutu Graduate, MAN 1 City Bandung